2021
DOI: 10.1101/2021.07.16.452604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climatic niche pre-adaptation in mainland Europe facilitated the colonization of Madeira by ivies (Hedera L., Araliaceae)

Abstract: Background and aims: The way plants cope with biotic and abiotic selective pressures determines their success in the colonization of remote oceanic islands, which ultimately depends on the phylogenetic constrains and ecological response of the lineage. In this study we aim to evaluate the relative role of geographical and ecological forces in the origin and evolution of the Madeiran ivy (H. maderensis). Methods: To determine the phylogenetic placement of H. maderensis within the western polyploid clade of Hede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…An analysis of the climatic niche of the Madeiran ivy revealed a preference for warm places with high isothermality and humid summers. Interestingly, these climatic preferences largely overlap with those of H. iberica (Alonso et al, 2022).…”
Section: Cistus Monspeliensismentioning
confidence: 89%
See 4 more Smart Citations
“…An analysis of the climatic niche of the Madeiran ivy revealed a preference for warm places with high isothermality and humid summers. Interestingly, these climatic preferences largely overlap with those of H. iberica (Alonso et al, 2022).…”
Section: Cistus Monspeliensismentioning
confidence: 89%
“…A recent phylogenomic study using the next-generation sequencing technique genotyping-by-sequencing (GBS) clarified the phylogenetic placement and colonization history of H. maderensis (Alonso et al, 2022). This study revealed that the Madeiran ivy is phylogenetically nested within the south-western Iberian endemic H. iberica…”
Section: Cistus Monspeliensismentioning
confidence: 97%
See 3 more Smart Citations